2014
DOI: 10.5603/nmr.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

The own method and program of isotopic quantitative assessment of perfusion in muscles of upper limbs

Abstract: BACKGROUND:The issue of blood flow in muscles has been dealt with for many years. However, most often it was assessed qualitatively with standard vascular examinations. The quantitatively perfusion assessment is indispensable in the normal and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…99m Technetium-sestamibi ( 99m Tc-MIBI) single-photon emission computed tomography (SPECT/CT) SPECT/CT is a widely used method for myocardial perfusion as it is able to reflect blood perfusion of the myocardium [13]. Several studies have revealed its role in evaluating the perfusion and mitochondrial function in skeletal muscles [14][15][16]. Recently, our center has established a screening method based on 99m Tc-MIBI SPECT/CT in CD [17].…”
Section: Introductionmentioning
confidence: 99%
“…99m Technetium-sestamibi ( 99m Tc-MIBI) single-photon emission computed tomography (SPECT/CT) SPECT/CT is a widely used method for myocardial perfusion as it is able to reflect blood perfusion of the myocardium [13]. Several studies have revealed its role in evaluating the perfusion and mitochondrial function in skeletal muscles [14][15][16]. Recently, our center has established a screening method based on 99m Tc-MIBI SPECT/CT in CD [17].…”
Section: Introductionmentioning
confidence: 99%